'Unboxing' videos: co-construction of the child as cyberflâneur. Issue 3 (3rd May 2016) - Marsh, Jackie
Abstract : This paper draws on data from a study of a four-year-old child, Gareth, in his first year of formal schooling in England. The aim of the study was to identify the nature of Gareth's literacy practices across home and school spaces. The focus for this paper is an analysis of one aspect of Gareth's home digital literacy practices: his repeated viewings at home of 'unboxing' videos on YouTube. These include videos that feature the unpacking of commercial products. It is argued that the child viewer/reader is co-constructed in these practices as cyberflâneur and that this mode of cultural transmission is a growing feature of online practices for this age group in the twenty-first century. The paper addresses issues concerning young children's online practices and their relationship to material culture before analysing the growth of interest in peer-to-peer textual production and consumption in the digital age.